Viability of preloaded Descemet membrane endothelial keratoplasty grafts with 96-hour shipment. Issue 1 (20th May 2021) - Chen, Conan; Solar, Steven Jared; Lohmeier, John; Terrin, Staci; Baliga, Satya; Wiener, Batya Gold; Lewis, Daniel Schouten; Chiang, Eric; Barnes, Kali Alexandra; Chaurasia, Akash; Eghrari, Allen O
Abstract : Objective: To assess feasibility and compare the effects of 96-hour shipment of Descemet membrane endothelial keratoplasty (DMEK) grafts as a scroll or a tri-fold on cell viability. Methods and analysis: DMEK grafts were prepared at the Rocky Mountain Lions Eye Bank. Twenty pre-stripped DMEK grafts, paired from 10 donors, were either tri-folded in an endothelium-in configuration using microforceps and loaded into a plastic Treyetech cartridge, or suctioned in a scrolled endothelium-out configuration into a modified Jones Tube. Grafts were shipped via FedEx to a secondary location and back for 48 hours each way, resulting in a total shipping time of 96 hours. After shipping, grafts were removed from inserters onto glass slides and unfolded using viscoelastic with endothelium facing upwards. Calcein-AM stained grafts were imaged with a fluorescent microscope and endothelial cell loss (ECL) was measured using trainable segmentation in Fiji by a masked grader. Results: A total of 20 grafts were shipped for 96 hours, split between preloaded tri-folded (n=10) and preloaded scrolled (n=10) tissues. No significant difference in ECL was observed across groups after prolonged shipping (14.8% vs 13.7% ECL respectively, p=0.68). Conclusion: For preloaded DMEK after 96 hours, both scrolled and tri-folded tissue demonstrated clinically acceptable levels of ECL. The data suggest a wider window of time for endothelial cell viability and is promising for the prospect of international shipment of preloaded grafts.